Multiplatform Antiperundungan sebagai Strategi Mewujudkan Madrasah Inklusi dan Ramah Anak - Nurul Ludfia Rochmah (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2023)
This study aims to find alternative ways of resolving cases of violence against children, especially bullying that can be applied to madrasah or schools in order to create inclusive and child-friendly madrasah. Much research has been done on this issue but it is still necessary to find new, more effective ways to reduce or even completely eradicate these bullying incidents. The aim is that schools or madrasah can choose the most effective method and provide significant results in eradicating cases of bullying. The research problem has been formulated as follows: 1) What are the challenges in realizing inclusive and child-friendly madrasah? 2) What are the multiplatform forms that can be used/utilized to create inclusive and child-friendly madrasah? This research is a type of literature study. Research data is taken by the process of grouping, allocating, organizing, and using variations of the literature. Data analysis used the qualitative analysis model of Miles and Huberman, including data reduction, data analysis, and drawing conclusions. This research produces six anti-bullying movement platforms that can be implemented in madrasah or schools. The presentations include (1) Empathy Skills Training Program with